Rendang as a Culinary Tourism Magnet: Leveraging Indonesia's Best Food for Destination Branding and Economic Impact in West Sumatra (International Journal of Economics and Management Research, 2024)
This study employs a Systematic Literature Review (SLR) to critically assess the strategic utility of Rendang (the globally celebrated Minangkabau dish) as a central asset for culinary tourism, destination branding, and regional economic development in West Sumatra, Indonesia. The analysis systematically synthesizes evidence concerning the dish's gastronomic, socio-cultural, and economic impacts, framed within three core thematic areas: Socio-Cultural Rigor, Gastronomic Innovation, and Destination Branding and Value Creation. Findings confirm that Rendang's recurring recognition as a world-class dish provides a powerful competitive edge. Its success is fundamentally rooted in its unique flavor profile, its adaptability, and its deep cultural significance, embodying Minangkabau philosophical virtues. Strategically, Rendang functions as a potent vehicle for destination branding, transforming passive consumption into active cultural immersion through integrated culinary tourism experiences. Economically, the Rendang industry in hubs like Payakumbuh fosters measurable growth by supporting local Micro, Small, and Medium Enterprises (MSMEs), generating value-added products, and strengthening the regional tourism supply chain. The study concludes that Rendang is an indispensable asset for Indonesia's competitive advantage, requiring sustained policy support for SME capacity, integrated tourism product development, and the long-term maintenance of cultural authenticity within sustainable and Halal tourism frameworks.